2004
DOI: 10.1104/pp.103.036368
|View full text |Cite
|
Sign up to set email alerts
|

CINCINNATA Controls Both Cell Differentiation and Growth in Petal Lobes and Leaves of Antirrhinum

Abstract: To understand how differentiation and growth may be coordinated during development, we have studied the action of the CINCINNATA (CIN) gene of Antirrhinum. We show that in addition to affecting leaf lamina growth, CIN affects epidermal cell differentiation and growth of petal lobes. Strong alleles of cin give smaller petal lobes with flat instead of conical cells, correlating with lobe-specific expression of CIN in the wild type. Moreover, conical cells at the leaf margins are replaced by flatter cells, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
126
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(135 citation statements)
references
References 25 publications
4
126
0
5
Order By: Relevance
“…CYC and the related DICH gene prevent cell division in specific floral organs, and cyc/dich mutants have reduced floral bilateral symmetry (11,19). CIN genes restrict cell proliferation at the margins of the developing leaf primordial, and cin mutants have crinkly leaves showing excessive proliferation at the leaf margin (13,21). TB1, the only maize TCP gene characterized so far, is reported to repress axillary meristem development, consistent with tb1 mutants having excessive vegetative lateral branches (10).…”
Section: Discussionmentioning
confidence: 95%
“…CYC and the related DICH gene prevent cell division in specific floral organs, and cyc/dich mutants have reduced floral bilateral symmetry (11,19). CIN genes restrict cell proliferation at the margins of the developing leaf primordial, and cin mutants have crinkly leaves showing excessive proliferation at the leaf margin (13,21). TB1, the only maize TCP gene characterized so far, is reported to repress axillary meristem development, consistent with tb1 mutants having excessive vegetative lateral branches (10).…”
Section: Discussionmentioning
confidence: 95%
“…The decreased leaf size in these plants was due to reduction in both cell proliferation and cell expansion, whereas enlarged petals resulted from increased cell expansion (26). Furthermore, the class II TCP factor CIN reduces growth in Antirrhinum leaves but promotes the growth of petals (20).…”
Section: Gerbera Tcp Factors Form a Clade Independent From Antirrhinumentioning
confidence: 95%
“…The expression of CYC and DICH is restricted to the dorsal domain of the flowers to establish bilateral petal symmetry and to arrest the development of the dorsalmost stamen (12,13). CIN arrests the growth of Antirrhinum leaf margins but also affects differentiation of epidermal cells and growth of petal lobes through effects on cell proliferation (20).…”
mentioning
confidence: 99%
“…This TCP domain is most similar to the domain present in CIN A. majus (data not shown), which indicates that InTCP4 may take part in the regulation of similar processes. The CIN gene is responsible for regulating the growth of the leaf blade and influencing the morphogenesis of flower petals (Crawford et al 2004). Similar functions are also played by another gene with high similarity to the nucleotide sequence InTCP4 of I. nil, namely LA from S. melongena.…”
Section: Discussionmentioning
confidence: 94%
“…TCP4 and miR319a, A. thaliana regulate the normal development of stamens and petals (Schommer et al 2008;Nag et al 2009). Analysis of cin mutants in Antirrhinum showed that the miRNA-regulated TCP gene, CIN, affects petal lobe development by controlling epidermal cell differentiation and growth (Crawford et al 2004).…”
Section: Discussionmentioning
confidence: 99%